Biomechanics and measurement on archery athlete: balancing body posture - Ahmad Taufiq, Ayub (2013)
Body balance is a very important aspect especially in a precision sports like archery. However this balance might be affected by the stance and foot positioning by the archers themselves. The main purpose of this study is to study the correlation between the foot positioning and its effect on postural stability during arrow releasing in archery with the accuracy of arrow being shot. 15 archers ranging from beginners and elite were involved in this study. The time taken for the archers to draw and aim until arrow release was measured using the time frame from the high speed camera. The postural sway and the force changes on front left foot on legs were recorded using force platform for every single arrow shot. The postural sway on the X-axis of force plate is the movement parallel to the target face (side to side) is denoted by X-X and the sway on the Y-axis of force plate is the movement perpendicular to the target face (front-back) is denoted by X-Y. The archers were asked to perform 3 arrow shots from a distance of 7 meters to the target. From the correlation analysis, it was found that the foot angle has a positive correlation with the score shot by the archers. It is also found that archers with lower tendency of X-X and X-Y have a better and consistent result as compared to the archers with higher postural sways changes. An analysis on differences in postural sway changes of recurve and compound bow was also done and it was found that the difference in bow type used caused different effects on the postural sway changes pattern of the archers. Based on the result, it was also found that there was a weight changes acting on the front left foot of the archer after the arrow release.